INT-004 Chronic hepatitis C: information brochure for patients under new direct acting antivirals. (25th February 2017) - Domngang, D; Lorent, S; Moreno, C
Abstract : Background: Clinical research for the treatment of chronic hepatitis C has evolved greatly with the introduction on the European pharmaceutical market of new oral direct acting antivirals (DAAs). Despite the fact that new DAA agents have fewer side effects, it is important to provide appropriate information to patients at initiation of treatment. Purpose: To develop and implement a therapeutic education tool for patients with chronic hepatitis C, and to provide accurate information during the pharmaceutical consultations organised at the hospital. Material and methods: The following steps were followed. Design viral hepatitis C brochure after review of: Scientific literature on chronic hepatitis C and new oral DAA agents. Recommendations on treatment of hepatitis C 2015 of several associations involved in the study of the liver (EASL and AASLD). Write new information sections for DAAs for the following drugs: siméprévir–sofosbuvir–ombitasvir+dasabuvir+paritaprevir/ritonavir–ledipasvir+sofosbuvir. Validate the therapeutic education tool by hospital pharmacists and gastroenterologists involved in the treatment of chronic hepatitis C. Results: The edition of the final patient information brochure (format A6) contained several sections, such as: General information Chronic hepatitis C Introduction Viral hepatitis C and virus Viral hepatitis C and treatment Viral hepatitis C and drug information Depending on the patient's medication Conclusion: Implementation of this information brochure allowed the hospital pharmacist to provide well summarised information on hepatitis C virus treatment. It is a useful tool during pharmaceutical consultations with chronic hepatitis C patients. The personalised information booklet provided to the patients can also be shared at home with the family, allowing them to have more details on hepatitis C disease and on the patient's drug regimen. References and/or acknowledgements: EASL (European Association for the Study of Liver): recommendations on treatment of hepatitis C2015. AASLD (American Association for the Study of Liver Diseases): recommendations on treatment of hepatitis C 2015. Summary of DAAs characteristics 2015. No conflict of interest